2019
DOI: 10.1111/cdoe.12467
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of systemic exposure associated with molar incisor hypomineralization

Abstract: Objective: To evaluate systemic exposures associated with molar incisor hypomineralization (MIH). Methods: This systematic review was performed using published observational studies that evaluated the systemic exposures associated with MIH. The sources of articles searched were PubMed, Scopus, Web of Science, LILACS, BBO, Cochrane Library and Grey literature. The risk of bias was analysed according to the Newcastle-Ottawa Scale for quality assessment. The meta-analysis was performed considering the exposures d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
3
22

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 52 publications
8
77
3
22
Order By: Relevance
“…Further efforts to address these challenges are warranted given the double attractions of gaining unprecedented spatiotemporal resolution (i.e., biomarker analysis of individual opacities) and identifying a narrower risk window for MH. Presently, aetiological investigations are hampered by poor understanding of the vulnerability period (reportedly extending from late prenatal to 3-4 years old for 6-year molars; Beentjes et al, 2002;Fagrell et al, 2013;Silva et al, 2016;Fatturi et al, 2019) during which myriad maternal and childhood illnesses prevail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further efforts to address these challenges are warranted given the double attractions of gaining unprecedented spatiotemporal resolution (i.e., biomarker analysis of individual opacities) and identifying a narrower risk window for MH. Presently, aetiological investigations are hampered by poor understanding of the vulnerability period (reportedly extending from late prenatal to 3-4 years old for 6-year molars; Beentjes et al, 2002;Fagrell et al, 2013;Silva et al, 2016;Fatturi et al, 2019) during which myriad maternal and childhood illnesses prevail.…”
Section: Discussionmentioning
confidence: 99%
“…Longheld dogma maintains that demarcated opacities result from systemic disturbance of enamel-forming cells (ameloblasts) during the hardening (maturation) stage of enamel formation (Suckling, 1989;Suga, 1989;Jalevik et al, 2001;Weerheijm, 2003;Alaluusua, 2010;Fagrell et al, 2013;Babajko et al, 2017). Yet, despite bolstering general links to childhood illness, numerous epidemiological and laboratory studies have failed to identify a specific cause or pathomechanism (Alaluusua, 2010;Silva et al, 2016;Fatturi et al, 2019;Silva et al, 2019). In 2010, two proteomic investigations showed that chalky enamel opacities contained unusually high amounts of protein, including serum albumin and other derivatives of blood and saliva (Farah et al, 2010;Mangum et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The staggering prevalence is globally 15% but 30% in the US [ 128 , 129 ]. Although the etiology of MH is still unknown, it is clear that an excess of retained organic matter compromises enamel mineralization [ 92 , 130 , 131 , 132 , 133 , 134 ]. The affected children experience severe pain and sensitivity and MH teeth are prone to caries, abrasion and fracture requiring surface coverage with fillings or replacement of the entire tooth crown or tooth extraction.…”
Section: Chalky Teeth and Serum Albumin In Enamelmentioning
confidence: 99%
“…Different systematic reviews concluded that most of the previously studied environmental factors that were believed to be risk factors for MIH did not fully explain the disease etiology [5,26,27]. In contrast, etiological factors associated with enamel forming genes [2,28] or in immune response-related genes [28,29] have been reported to play a role in the condition's onset.…”
Section: Introductionmentioning
confidence: 99%